Poor risk advanced renal cell carcinoma: Outcomes from a registry in a tertiary cancer center - Anant Ramaswamy; Amit Joshi; Vanita Noronha; Vijay Patil; Arvind Sahu; Deepan R Manickam; Rushabh Kothari; Nilesh Sable; Archi Agrawal; Santosh Menon; Kumar Prabhash (Indian Journal of Medical and Paediatric Oncology)
Background: Poor-risk advanced Renal cell carcinoma (RCC) are an under-evaluated and difficult to treat subset of patients with poor prognosis. While Temsirolimus is the approved first line therapy for this category, Tyrosine kinase inhibitors (TKIs) are also commonly uses as initial treatment. We present an analysis of poor-risk advanced RCC treated in our institute. Materials and Methods: Patients diagnosed as poor-risk (as per Heng criteria) advanced RCC from June 2008 to December 2015 were analysed for baseline demographics, treatment received, toxicity (primarily Grade 3 and Grade 4), response rates (RR) and survival. Results: 60 patients (43 males, 17 females) with a median age of 53 years were included for final analysis. Median ECOG PS was 1, clear cell was the predominant histology (63.3%), and 46.7% of patients had greater than 2 sites of metastases. Sorafenib, Sunitinib, Temsirolimus and Pazopanib were used to treat 43.3%, 36.7%, 8.3% and 6.7% of patients respectively, while 3 patients were offered upfront best supportive care. Common adverse events included skin rash (31.5%), HFS (Grade 2 and 3 - 30.8%), mucositis (26.3%), hypertension (24.5%), and dyslipidaemias (22.8%). 41 patients were available for response - overall response rate observed was 15%, while clinical benefit rate was 50%. Median progression free survival was 5.78 months (4.67-6.89) and median overall survival (OS) was 10.05 months (7.31-12.79). Conclusion: A majority of poor-risk metastatic RCC patients in our study were treated with TKIs and the survival outcomes appear to suggest that this strategy is a feasible alternative to Temsirolimus in the Indian setting.